Bibliographic work of Ivan Franjo Jukić and the end of cultural history. Bibliographies as a source for the history of books and cultural history (Libellarium: journal for research in the field of information and related sciences, 2009)
Bosnian Franciscan Ivan Franjo Jukić (1818-1857) died a hundred and fifty years ago. He was one of the most prominent figures in the 19th century cultural life of Bosnia and Herzegovina, credited with the development of a wide-ranging set of aspects of cultural life in Bosnia and Herzegovina, organised in the unpropitious conditions of the Turkish occupation. Among other things, he studied the non-religious cultural history of Bosnia and Herzegovina and, in particular, the literary work of his Franciscan predecessors who were active in pastoral work for many years on the entire Croatian cultural territory and, in some periods, outside this territory. Preaching in the tongue of the people, they contributed greatly to the standardisation of the Croatian language and to the development and use of bosanica as a specific form of the Croatian Cyrillic script. Jukić was one of the first, if not the first Croatian student of this script. The study of bosanica was an inspiration to him to collect and bibliographically describe books written in this script and, also, books written in the Latin script. Thus emerged the core of his text, Bosnian Literature, which is in fact a general bibliography of Bosnia and Herzegovina. It was the first book to set as a criterion the secular and not the religious borders of Bosnia. The text was published in two installments in the first literary journal in Bosnia and Herzegovina, Bosanski prijatelj, started and edited by Jukić.The paper is to commemorate the anniversary of his death. It provides an insight into the results of the bibliographic, cultural and historic study of Jukić’s text. The bibliographic study focuses on the bibliographic structure, bibliographic descriptions and on the criteria applied in the selection of the material. The bibliographic features are analysed as part of the cultural and historic context, in the synchronic and diachronic sense of the word. The method applied in the contextualised bibliographic analysis provides background for the study of some of Jukić’s less well known standpoints, relevant for the criteria employed in the selection of the materials for the national retrospective bibliography.The need to approach the matter from cultural and historic aspects is in correspondence with Jukić’s devout support of the Illyrian movement. This movement promoted the unity of the Southern Slavs, calling them all Illyrians and regarding them as basically a single people speaking the same language. As one of its focuses, the movement also promoted bibliographic work. Tracing back this orientation leads us to its source, the German Romanticism, which relied on the common language for the building of unity of the disunited German lands, and promoted the primacy of culture over the primacy of politics. With the German people this unity was successful, whereas the political reality, in part shaped by bloody wars, was a vivid proof of the failure of the Illyrian, and later, of the Southern Slavic idea. The course of research done for this paper was greatly affected by this historical fact, especially evident in the criteria for the selection of the bibliographic material.Starting off with the Illyrians’ understanding of what ”the regional’’ denotes, Jukić not only accepted the identification of the Illyrians and the Southern Slavs as one and the same entity, but he also treated Bosnia’s Muslims as the ”glorious Illyrian people’’, not only territorially but also ethnically. Students of the cultural and political history of Bosnia did not agree with Jukić’s arguments, and the cultural and historical processes proved him wrong by developing in directions that Jukić could not have foreseen or expected. The outcome of the Turkish siege of Bosnia was, namely, in the identification of the religious with the national. So it happened that Jukić, as a Catholic, is thought of as a Croatian culturalist and bibliographer, and a member of the Croatian ethnic group, irrespective of the fact that, territorially speaking, he belongs to Bosnia and Herzegovina and is a member of that state’s cultural elite.A bibliographic analysis makes up the core of the paper, and the core is framed by a methodologically immanent, modern cultural and historical context. Furthermore, inspired by Jukić’s Illyrian orientation, the analysis is also evaluated briefly from the point of view of the post-modern cultural and historic constructivism.
Keywords: Ivan Franjo Jukić; bibliography; bibliographic analysis; Bosnian Franciscans; Bosanski prijatelj; Illyrian movement